PartiuDoarSangue - Uma Plataforma Web e Aplicativo Mobile para Captação e Gestão Inteligente de Doação de Sangue e Hemocomponentes - Rodrigues, Thiago Abreu; Silva Jr. , Orlando; Pereira, Adriano C. M. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2017)
This work discusses the development of a new platform and mobile application (app) to minimize the problem of lack of blood donation. In order to do this, interviews were conducted with blood bank professionals and we perform a specific research to identify the best solution for this problem, which can be considered one of the most important demands for Brazilian Health Service. We design and develop a electronic platform, containing a Web and a mobile application (#PartiuDoarSangue) whose main characteristic is to connect donors to those who need blood donation. Through this platform it was possible to identify a great acceptance from users, providing a tool to centralize the donor registry and link them to those who need donation, besides allowing a greater diffusion of this cause. The platform achieved its goal, as demonstrated by our real validation blood donation campaign and it is available in all Brazilian Federal Units.